How palytoxin transforms the Na + ,K + pump into a cation channel - Ryuta Kanai; Naoki Tsunekawa; Flemming Cornelius; Bente Vilsen; Chikashi Toyoshima (Proceedings of the National Academy of Sciences, 2025)
Palytoxin (PTX), a potent marine toxin, has long been known to transform Na + ,K + -ATPase (NKA), an indispensable ion pump, into a nonselective cation channel. It has been postulated that PTX takes control of the two gates on either side of a channel-like pore. These gates normally open and close alternately, synchronized with chemical events, never opening simultaneously. A critical question is whether palytoxin takes over the control of the two gates or creates a new pathway. Here, we present structures of NKA with bound palytoxin in three different states. PTX binds to NKA in E2P, occupying the physiological Na + exit pathway, similar to istaroxime, a new-generation cardiotonic steroid. Adding Na + and ATP/ADP to the NKA·PTX complex induces an open channel traversing the entire membrane alongside the physiological ion pathway. As AlF x , a stable transition state analog of phosphate replaces phosphate in the NKA·PTX complex preformed in E2P, the complex appears to undergo the normal reaction cycle from E2P to E1· n Na + . PTX occupies the space between the transmembrane helices M4 and M6, thereby preventing the closure of the extracellular half of the ion pathway. These structures demonstrate that the architecture of NKA is fundamentally different from “a pore with two gates.” Each half of the ion pathway comprises three segments, including a movable component that plays a pivotal role in translocating the bound cations by connecting the constant part to an appropriate inlet. The ion pathway of NKA transforms dynamically, ensuring that the two halves never exist simultaneously.